'The theory doesn’t work here': the teenage bedroom in a residential special school - Nick Pike (Scottish Journal of Residential Child Care)
Drawing on non-participant ethnographic observation, this paper explores some of the challenges for residential child care staff of operationalising an 'ordinary living' policy in a residential special school for children with complex learning difficulties and challenging behaviour. In particular, it explores the complex and multi-faceted uses made of teenage residents' bedrooms and describes a critical role for child care practitioners in making sense of competing priorities and constructing a workable practice framework.